Comparison of critical speed and D' derived from 2 or 3 maximal tests - Kordi, M.; Menzies, C.; Galbraith, A. (International Journal of Sports Physiology and Performance, 2019)
Purpose: The hyperbolic distance-time relationship can be used to profile running performance and establish critical speed (CS) and D' (the curvature constant of the speed-time relationship). Typically, to establish these parameters, multiple (3+) performance trials are required, which can be highly fatiguing and limit the usability of such protocols in a single training session. This study aimed to compare CS and D' calculated from a 2-trial (2-point model) and a 3-trial (3-point model) method. Methods: A total of 14 male distance runners completed 3 fixed-distance (3600, 2400, and 1200 m) time trials on a 400-m outdoor running track, separated by 30-min recoveries. Participants completed the protocol 9 times across a 12-mo period, with approximately 42 d between tests. CS and D' were calculated using all 3 distances (3-point model) and also using the 3600- and 1200-m distances only (2-point model). Results: Mean (SD) CS for both 3-point and 2-point models was 4.94 (0.32) m/s, whereas the values for D' were 123.3 (57.70) and 127.4 (57.34) m for the 3-point and 2-point models, respectively. Overall bias for both CS and D' between 3-point and 2-point model was classed as trivial. Conclusion: A 2-point time-trial model can be used to calculate CS and D' as proficiently as a 3-point model, making it a less fatiguing, inexpensive, and applicable method for coaches, practitioners, and athletes for monitoring running performance in 1 training session.